Analysis of the diversion requirements from the deduru oya reservoir in sri lanka - Sampath, D.S.; Weerakoon, S.B.; Mishra, B.K.; Herath, S. (University of Jaffna, 2014)
The Deduru Oya reservoir project which is under construction is aimed to improve the livelihood of farmers in parts of the North Western Province by increasing the productivity of its land by regulating and diverting the Deduru Oya water by two main canals. The proposed Left Bank (LB) canal which is 44.1 km long with a discharge capacity of about 7.1 m3 /s at the intake will supply water to augment about 136 existing storage-based minor irrigation systems in the left bank of the Deduru Oya river. This study is focused on the analysis of the diversion requirements of the proposed reservoir. For each of the 136 rain-fed minor reservoirs(tanks) that will be supplied water by the LB canal, the relevant catchment areas, storage areas, natural streams, land use patterns and cascades were identified for modeling the system. Topographic, geology and land use details were collected from the digital data of the Survey Department of Sri Lanka and Arc GIS 9.2 was used as a tool for spatial analysis. HEC-HMS (Hydrologic Engineering Center– Hydrologic Modeling System) version 3.0.1 was calibrated and verified for the Tittawella Tank, which is a minor tank in Kurunegala District and also for the Deduru Oya river Catchment. HEC-HMS model was then used to develop rainfall runoff model for each of the rain-fed irrigation tank catchment and the Deduru Oya reservoir catchment. WEAP21 version 3.43 (Water Evaluation And Planning) model was used to study the water requirement from LB canal. The LB development area would require 62 MCM annually through the LB canal as a supplement to meet the LB irrigation demand of the existing and proposed new development areas in dry year while annual RB trans-basin diversion is 79 MCM, and annual downstream release for hydropower, irrigation and environmental requirements is 502 MCM in 2009. With long term forecast rainfall data, the WEAP model can be used for predictability studies in the Deduru Oya LB development areas. The model developed is a useful tool for planning water resources development in the Deduru Oya reservoir project.
Keywords: Deduru oya project; HEC-HMS; Weap; Irrigation development